The Power of Sugesti in Traditional Javanese Healing Treatment - Triratnawati, Atik; Wulandari, Arsanti; Marthias, Tiara (KOMUNITAS: International Journal of Indonesian Society and Culture, 2014)
This paper aims to explore the beliefs in society toward traditional healing regardless of the more accessible, affordable and improved modern health services. This ethnographic study was conducted in Yogyakarta in 2013-2014. Phenomenological approach was used to analyze the data using the theory of health seeking behavior as the guiding principle of this research. The main factor influencing Javanese community’s belief in traditional healing was the power of placebo effect. Placebo can arise from both the patient and the healer. Additionally, other factors such as compatibility between the patients and the healer, patient’s aversion to doctor’s therapy, and the fact that traditional treatment is cheaper, easier, and more effective than modern medicine were the main considerations for patients in choosing traditional treatment. The benefit of psychotherapy provided through traditional medicine is in the form of life advices or counseling. In addition, healers’ attentiveness in listening to patients’ complaints was also the main appeal of the traditional health care service.Tulisan ini mengupas kepercayaan masyarakat pada penyembuhan medis tradisional meski pelayanan kesehatan modern semakin mudah diakses, murah/gratis pembiayaannya serta ditingkatkan pelayanannya. Studi etnografis ini dilakukan di DIY tahun 2013-2014. Pendekatan fenomenologi digunakan untuk menganalisis data disertai teori health seeking behavior. Kunci kepercayaan masyarakat Jawa berobat ke penyembuh tradisional adalah pengaruh sugesti. Sugesti muncul baik dari penderita maupun penyembuh. Selain itu faktor cocok, takut dengan terapi dokter serta murah, mudah dan manjur juga menjadi pertimbangan pasien ke pengobatan tradisional. Manfaat psikoterapi berupa nasihat, wejangan maupun saran serta kemampuan penyembuh tradisional mendengar curahan hati pasien menjadi daya tarik lain pasien merasa cocok ke pengobatan non medis.